Evaluation And Analysis Of The Integration Of Islamic Values Through Religious Practices In Building Student Character Atmi Darul Hikmah Mojosari - Adzim Baqi, Subkhana; Bahrul Ulumiyah, Miftakhus Sifa’ (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
The formation of children's character based on spiritual education with the integration of Islamic values serves as a fundamental foundation for preparing a nation's generation that is moral, ethical, and high-quality. This study aims to deeply uncover religious practices in the character formation of children at the elementary school level, MI Darul Hikmah Mojosari. This research uses a qualitative method with a phenomenological approach, then analyzed using Kohlberg's theory of value internalization. The results of the study indicate that children's character problems include bullying, lack of respect for teachers, fights between friends, cheating, immoral behavior, and the habit of lying. These problems are caused by several factors, including a shallow understanding of religion, lack of supervision and guidance from family, school, and society, as well as negative environmental influences. Observing this phenomenon, MI Darul Hikmah Mojosari implements various religious programs such as congregational prayers, Traveling Yasin Recitation, Maulid Diba’i, Quranic Reading and Writing (BTQ), recitation of the Kitab Mabadi’ul Fiqh, and Istighasah as a means of forming students' Islamic character. The implementation of these programs has an impact on increasing students' discipline, social care, and religious understanding. However, there are some challenges such as the continuity of religious practices outside the school environment. The use of Kohlberg's analysis in this study shows that the process of internalizing Islamic values at MI Darul Hikmah Mojokerto takes place through cognitive, affective, and conative stages. The success of student character formation is influenced by teacher responsibility, school monitoring systems, parental roles, and community involvement. Good synergy among all parties is expected to realize students' personalities that are moral, ethical, and civilized in accordance with Islamic values.